Will the Levelling Up White Paper (LUWP) drive reform of national innovation policy and practice?. (February 2022) - Marlow, David
The Levelling Up White Paper (LUWP) is intended to drive local economic growth and development, particularly in left-behind places. It proposes policies and investments in innovation infrastructure and services as an explicit mission and key component of the LU reform agenda. This paper, however, suggests that, without systemic behaviour and culture change in national innovation institutes and their funders, the LUWP will produce few if any results of game-changing significance. Based on a project to explore how a Research Council and one of its core funded institutes should improve local impact and prepare for the LUWP, the paper explores practical changes that need to be considered to make LUWP place-based innovation ambitions a reality. It discusses the structures and processes that national institutes and programmes might need to transition from interventions that have local impacts incidentally by accident of where they are taking place, to purposeful place-based growth and development. It then suggests the capabilities required to deliver this well – which has major implications for innovation funders. The LUWP's good intentions for more impactful place-based innovation requires new tools and techniques, experimentation and learning-by-doing, and proper resourcing – robustly tested and evaluated by Local Economy research and practitioner communities.